2017
DOI: 10.5713/ajas.17.0089
|View full text |Cite
|
Sign up to set email alerts
|

Replacing groundnut cake with gluten meals of rice and maize in diets for growing Sahiwal cattle

Abstract: ObjectiveThis experiment investigated the effect of isonitrogenous replacement of groundnut cake (GNC) by rice gluten meal (RGM) and maize gluten meal (MGM) at 75% level on nutrient intake, apparent digestibility, growth performance and related blood constituents in growing Sahiwal cattle.MethodsEighteen Sahiwal calves were divided into three groups, based on average body weight (87.24 kg) and age (6 to 12 mo), and treatments were assigned to the different groups randomly. The first group (GP-I) was kept as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Because it contains 50% CP, it has the potential to be utilized as an elective to soybean in poultry diets for economic production (Wani et al 2018) and 3330 kcal/kg metabolizable energy (ME) (Metwally and Farhat, 2015). Some previous studies of using RGM as alternative protein source were done in broiler (Metwally and Farahat, 2015; Wani, 2018 and Dinani et al 2020) and Cattle (Malik et al, 2017). Betaine minimum and maximum temperatures, the relative humidity and the temperature humidity index ranged 25.5-33.5°C, 62-75% and 87.5-93.5, respectively.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because it contains 50% CP, it has the potential to be utilized as an elective to soybean in poultry diets for economic production (Wani et al 2018) and 3330 kcal/kg metabolizable energy (ME) (Metwally and Farhat, 2015). Some previous studies of using RGM as alternative protein source were done in broiler (Metwally and Farahat, 2015; Wani, 2018 and Dinani et al 2020) and Cattle (Malik et al, 2017). Betaine minimum and maximum temperatures, the relative humidity and the temperature humidity index ranged 25.5-33.5°C, 62-75% and 87.5-93.5, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…These are con rmed by Amagliani et al (2019) who demonstrated that rice protein meal has excellent physicochemical properties which make it as functional and value-added ingredient. As well, it contains favorably good amino acids pro le with relatively higher methionine (Malik et al 2017). The improvement of CP digestibility is related to the methionine sparing effect of betaine may improve the effective use of dietary protein Eklund et al (2005).…”
Section: Nutrients Digestibilitymentioning
confidence: 99%
“…Kumar et al (2016) found that RGM could replace groundnut cake in the concentrate mixture of growing calves up to 75% level without any adverse effects on growth performance and nutrient utilization. Malik et al (2017) reported that replacement of groundnut cake by RGM and maize gluten meal at 75% level did not affect feed intake, feed efficiency and average daily gain in growing Sahiwal cattle.…”
Section: Introductionmentioning
confidence: 96%
“…Groundnut cake contains about 40-45% crude protein and it promotes growth of animals. But, the protein in groundnut cake is deficient in lysine and methionine and having limited amount of tryptophan and threonine (Malik et al, 2017). Among plant protein sources, soybean meal is known for the highest feeding value due to both its high protein content and essential amino acids needed to meet the nutrient requirements of animals.…”
Section: Introductionmentioning
confidence: 99%